Systemic Barriers and Opportunities in Financial Inclusion: Lessons from Developing Regions - Widiastuti, C. Tri (Moneta : Journal of Economics and Finance, 2025)
Financial inclusion has gained global recognition as a cornerstone of sustainable economic development, particularly in developing economies where large segments of the population remain excluded from formal financial systems. This narrative review aims to synthesize evidence on the roles of microfinance, mobile banking, and policy approaches in advancing financial inclusion. A systematic search of academic databases, including Scopus, Google Scholar, and Web of Science, was conducted using targeted keywords to identify relevant studies published between 2010 and 2025. Inclusion criteria emphasized peer-reviewed works addressing financial access in developing countries, while methodological diversity encompassed quantitative, qualitative, and mixed-methods studies. Findings indicate that microfinance significantly supports poverty alleviation and women’s empowerment, though results vary across contexts and sometimes lead to over-indebtedness. Mobile banking demonstrates strong potential to expand financial access by lowering transaction costs and overcoming geographic barriers, with notable successes in India, Bangladesh, and Kenya. National policy frameworks create enabling environments that integrate financial innovations into broader economic strategies, yet challenges remain in ensuring active usage and consumer protection. Systemic barriers, including weak infrastructure, inconsistent regulation, and low digital literacy, persist as major obstacles. The discussion highlights the need for gender-sensitive policies, expanded literacy initiatives, and investments in infrastructure. Future research should examine long-term outcomes of inclusion strategies and the potential of emerging technologies such as blockchain. Overall, the review concludes that sustainable and inclusive financial systems require coordinated interventions that align access, capacity, and governance to achieve transformative impact.